Evaluation of cocoa (Theobroma cacao) clones at the artificial inoculation of Moniliophthora roreri in Tingo María, Perú - Paredes Espinosa, Richard (2022)
The objective of the study was to evaluate the reaction of Theobroma cacao clones to the artificial inoculation of Moniliophthora roreri, at the Tulumayo Experimental Station, Tingo María. Eleven “S” clonal hybrids and 3 “C” farmer collection clones were studied. Conidia of M. roreri were inoculated into 65-day-old fruits, protected for 48 h in a humid chamber. Incidence, external severity (SE) according to fruit damage in degrees were evaluated weekly, 0: healthy fruit, 1: hydrosis, 2: swelling, 3: necrosis, 4: mycelium that covers ¼ part of the stain and 5: mycelium that covers more than ¼ part of the stain, and internal severity (SI): percentage of necrotic grain in each fruit, the clones being compared by ANOVA and Tukey’s test (α = 0.05). The results show a high incidence in all the clones, with values of 91.67 to 100%. Clone S-19 showed the lowest SE, which was 2.64, while clones S-01, S-08, S-09, S-11, S-13, S-15, S-22; S-24, S-26, S-28, C-02, C-03, and C-29 reported values between 3.64 and 5. The SI, fluctuated from 4.18 to 5 in all the clones evaluated. It is concluded that the clones are classified as susceptible to M. roreri, however, despite the fact that clone S-19 succumbed to the disease, it was able to delay the disease and the production of spores, an important character in the field that allows increasing the interval of fruit removal and fungicide applications, reducing production costs, negative environmental effects and improving work efficiency.